Investigation of the luminescent properties of SiLiZn glass-ceramic phosphor doped Cr3+/Cr4+ - Sadowska, Karolina; Żmojda, Jacek Mariusz (Photonics Letters of Poland, 2025)
This study presents the development of Cr2O3 – doped glass-ceramic phosphors with the possibility of obtaining Cr³⁺/Cr⁴⁺ for broadband near – infrared (NIR) emission, targeting for potential applications in NIR phosphor – converted LEDs (pc – LEDs). Optimization of Cr₂O₃ doping and annealing conditions of glass-ceramic, we achieved emission in the range of NIR – I (700 – 950 nm) and NIR – II (1000 – 1700 nm) biological windows. Based on the luminescence measurements performed, in the glass sample, emission bands attributed to Cr³⁺ in an octahedral environment were observed with strong emission at 955 nm (corresponding to the transition 4T2 → 4A2), while emission of annealed glass – ceramics suggested the appearance of Cr⁴⁺ with a peak at 1250 nm (3T2 → 3A2). Full Text: PDF References V. Rajendran, T. Lesniewski, S. Mahlik, M. Grinberg, G. Leniec, et al., "Ultra-Broadband Phosphors Converted Near-Infrared Light Emitting Diode with Efficient Radiant Power for Spectroscopy Applications", ACS Photonics 6, 3215 (2019). CrossRef K. Sadowska, T. Ragiń, M. Kochanowicz, P. Miluski, J. Dorosz, et al., "Analysis of Excitation Energy Transfer in LaPO4 Nanophosphors Co-Doped with Eu3+/Nd3+ and Eu3+/Nd3+/Yb3+ Ions", Materials 16, 1588 (2023). CrossRef X. Wang, Z. Wang, M. Zheng, J. Cui, Y. Yao, et al., "A dual-excited and dual near-infrared emission phosphor Mg14Ge5O24:Cr3+,Cr4+ with a super broad band for biological detection", Dalton Trans. 50, 311 (2021). CrossRef M.-H. Fang, P.-Y. Huang, Z. Bao, N. Majewska, T. Leśniewski, et al., "Penetrating Biological Tissue Using Light-Emitting Diodes with a Highly Efficient Near-Infrared ScBO3:Cr3+ Phosphor", Chem. Mater. 32, 2166 (2020). CrossRef T. Gao, Y. Liu, R. Liu, W. Zhuang, "Research Progress and Development of Near-Infrared Phosphors", Materials 16, 3145 (2023). CrossRef T. Narendrudu, S. Suresh, G. Chinna Ram, N. Veeraiah, D. Krishna Rao, "Spectroscopic and structural properties of Cr3+ ions in lead niobium germanosilicate glasses", J. Lumin. 183, 17 (2017). CrossRef W.A. Pisarski, J. Pisarska, G. Dominiak-Dzik, W. Ryba-Romanowski, "Transition metal (Cr3+) and rare earth (Eu3+, Dy3+) ions used as a spectroscopic probe in compositional-dependent lead borate glasses", J. Alloys Compd. 484, 45 (2009). CrossRef Z. Xiao, S. Qin, X. Guo, X. Xu, W. Anaerguli, et al., "Efficient and broadband near-infrared emission of Cr<>sup>3+-doped glass-ceramics for near-infrared light sources applications", J. Lumin. 247, 118907 (2022). CrossRef